2020
DOI: 10.3390/cancers12051246
|View full text |Cite
|
Sign up to set email alerts
|

Beyond MicroRNAs: Emerging Role of Other Non-Coding RNAs in HPV-Driven Cancers

Abstract: Persistent infection with high-risk Human Papilloma Virus (HPV) leads to the development of several tumors, including cervical, oropharyngeal, and anogenital squamous cell carcinoma. In the last years, the use of high-throughput sequencing technologies has revealed a number of non-coding RNA (ncRNAs), distinct from micro RNAs (miRNAs), that are deregulated in HPV-driven cancers, thus suggesting that HPV infection may affect their expression. However, since the knowledge of ncRNAs is still limited, a better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 174 publications
0
30
0
Order By: Relevance
“…In particular, accumulating research data have demonstrated that the lncRNAs alterations in HPV infected cells was also crucial for the progression of cervical cancer. For example, a microarray analysis revealed that thousands of host lncRNAs had differential expression in oncogenic HPV-positive cells compared to the HPV-negative cervical cancer cell line [37]. Lots of lncRNAs were found to be differentially expressed in the HPV18 positive HeLa cells respect to C33A cell line [38].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, accumulating research data have demonstrated that the lncRNAs alterations in HPV infected cells was also crucial for the progression of cervical cancer. For example, a microarray analysis revealed that thousands of host lncRNAs had differential expression in oncogenic HPV-positive cells compared to the HPV-negative cervical cancer cell line [37]. Lots of lncRNAs were found to be differentially expressed in the HPV18 positive HeLa cells respect to C33A cell line [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted in recent times HPV-related cancer cases are increasing. Casarotto et al described the utility of non-coding RNAs, such as miRNAs in HPV-related cancer [30] . A colon or rectum related cancer is often termed as colorectal cancer which is associated with bowel movement and inflammation.…”
Section: Santarispharmamentioning
confidence: 99%
“…Since then, a large number of reports have found that lncRNAs play important biological functions, and lncRNAs have a wide range of tissue expression profiles and strong tissue expression specificity. Multiple studies have found that lncRNAs play key roles in tumorigenesis and development, and several lncRNAs are differentially expressed in cancers, including cervical cancer (5)(6)(7)(8). For example, the lncRNA LINC00673 has a carcinogenic effect in breast cancer (9,10), lung cancer (11,12), and gastric cancer (13) and exerts a tumor suppressive effect in pancreatic cancer (14).…”
Section: Introductionmentioning
confidence: 99%